2015
DOI: 10.1021/acs.orglett.5b01587
|View full text |Cite
|
Sign up to set email alerts
|

CuI/RhII-Catalyzed Tandem Convergent Multicomponent Reaction for the Regio- and Stereocontrolled Synthesis of γ-Oxo-β-amino Esters

Abstract: The first example of a highly regio- and stereoselective catalytic method for the three-component one-pot synthesis of highly functionalized α-vinylated γ-oxo-β-amino esters is disclosed. In this catalytic triad, the Cu(I)-catalyst selectively catalyzes the cycloaddition of the 1-alkyne and sulfonyl azide first resulting in the corresponding 1-sulfonyl-1,2,3-triazole. An α-imino Rh(II)-carbene is generated from an open-chain α-imino diazo of the triazole, and this species reacts with γ-hydroxy α,β-unsaturated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 40 publications
(18 reference statements)
0
22
0
Order By: Relevance
“…On the basis of the experimental results and previous reports, we propose a plausible mechanism in Scheme . Initially, N ‐sulfonyl‐1,2,3‐triazole 2a is converted into α‐diazo imine intermediate A by ring‐chain tautomerization; this intermediate subsequently reacts with the rhodium catalyst to afford α‐imino rhodium carbenoid intermediate B with the loss of molecular nitrogen.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…On the basis of the experimental results and previous reports, we propose a plausible mechanism in Scheme . Initially, N ‐sulfonyl‐1,2,3‐triazole 2a is converted into α‐diazo imine intermediate A by ring‐chain tautomerization; this intermediate subsequently reacts with the rhodium catalyst to afford α‐imino rhodium carbenoid intermediate B with the loss of molecular nitrogen.…”
Section: Resultsmentioning
confidence: 59%
“…Moreover, Fokin and co‐workers demonstrated a similar type of transformation with propargyl alcohols . Subsequently, Lee and co‐workers reported the regio‐ and stereocontrolled synthesis of γ‐oxo‐β‐amino esters starting from N ‐sulfonyl‐1,2,3‐triazoles and γ‐hydroxy‐α,β‐unsaturated esters . Furthermore, N ‐sulfonyl‐1,2,3‐triazoles have also been extended to Morita–Baylis–Hillman (MBH) adducts for the preparation of α‐methylene‐δ‐oxo‐γ‐amino esters .…”
Section: Introductionmentioning
confidence: 99%
“…Among them, 1,2,3‐triazoles, firstly explored as synthetic equivalents of azavinyl carbenes by Gevorgyan, Fokin, and co‐workers, have the capacity of the formation of unique rhodium(II)‐bound imino carbene intermediates I with the loss of dinitrogen, enabling numerous useful synthetic transformations . For example, the tandem insertion/[3,3]‐ sigmatropic rearrangement of N ‐sulfonyl‐1,2,3‐triazoles with allyl alcohol derivatives, give access to β‐amino and γ‐amino acid derivatives, which are highly valuable in many scientific areas . Nevertheless, the catalytic enantioselective version of this tandem process remains elusive.…”
Section: Methodsmentioning
confidence: 84%
“…To study the intrinsic aspects of the bimetallic catalyst system, we first conducted the reaction between the 1,2,3‐triazole 1 a and allyl alcohol ester 2 a in the presence of the Rh 2 (esp) 2 catalyst and 4 Å M.S . (Table , entry 1).…”
Section: Methodsmentioning
confidence: 99%
“…The utility of this method is demonstrated by an application to a formal synthesis of (–)‐ α ‐conhydrine. A study on the use of 2,3‐alkadienols is also reported [13]…”
Section: Introductionmentioning
confidence: 99%